Chyngyz Aytmatov’s Point of View about Cultural, Social, Economic and Communication Reasons of the Crisis of the World Literature - Vaskiv, Mykola; Bykova, Olha (Journal of History Culture and Art Research, 2020)
The article examines the problem of the complete decline of morality and culture under the pressure of mass consumption on the example of the work of the Kyrgyz writer Chyngyz Aytmatov. “The Brand of Cassandra” and “When the Mountains Fall (The Eternal Bride)” are Aytmatov’s last two novels. They were written after the collapse of the Soviet Union, and they were thoroughly analyzed in the article. The plot of the novel “The Brand of Cassandra” (1994) is based on the author’s thoughts on the world order after the collapse of the Soviet Union and the transformation of the bipolar confrontation between superpowers and their satellites. Aytmatov had comprehended the real issues of responsibility of each person for the crimes and sinfulness of the world philosophically deeply, becoming global in this work. In the novel “When the Mountains Fall (The Eternal Bride)” (2006), the writer, on the example of the life of snow leopard Jaabars and journalist Arsen Samanchin, reflects on the problems of complete loss of spirituality, destruction of moral landmarks, their reduction to material goods in the wild market to Central Asia. The object of the characteristic of the article also became the journalistic heritage of Ch. Aytmatov of the Soviet period, the innovation of which was that the author emphasized the real and inevitable threats to consumption and the dominance of mass culture in both capitalist and socialist society. It is noted that the Kyrgyz writer focused important attention in his work on the problems of moving “serious” literature to the periphery of the reader’s attention, the reluctance of the vast majority of individuals to address important issues of human existence, spiritual life. The main emphasis was placed on the fact that Ch. Aytmatov was deeply concerned with the dehumanization of society, subtly felt the crisis in which humanity found itself, concerned more with the accumulation of material goods than spiritual development.